Scientific bases of strength training for endurance performance - Mujika, I. (Science + Triathlon 2015 World Conference, 2015)
Performance in most endurance events is determined by the maximal sustained power production for a given competition distance, and the energy cost of maintaining a given competition speed. In shorter endurance events and during accelerations and sprint situations, anaerobic capacity and maximal speed may also contribute to performance. Strength training could thus contribute to enhance endurance performance by improving the economy of movement, delaying fatigue, improving anaerobic capacity and enhancing maximal speed (Ronnestad & Mujika 2014).